Sikap Dan Persepsi Mahasiswa Di Surabaya Terhadap Keputusan Pembelian Secara Online - Anita Asnawi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Driven by the development of a digital technological environment that is easy to access and use, more and more people prefer to carry out transactions online. This study tries to see how the attitudes and perceptions of the student segment in Surabaya influence online shopping decisions. The group of students was chosen on the basis that this is a very potential market segment in the current era of digitization, as they can quickly learn and understand developments in digital technology and are able to use apps well on their digital devices. Attitude variables include indicators of consumer confidence, consumer sentiment, and consumer reactions to online shopping activity. The perception variable is made up of indicators of online shopping experience, consumer needs, values ​​adopted and consumers' expectations for online shopping. The results of the analysis of this study indicate that there is a partially significant influence between each attitude variable and perception variable on Surabaya students on online shopping decisions. In addition, the attitude variable and the consumer perception variable together were found to have a significant effect on online shopping decisions.